THE EFFECTIVENESS OF INDONESIAN HONEY STIMULATE FIBROBLAST CELL VIABILITY AND MIGRATION THAT COULD POTENTIAL PROMOTE WOUND HEALING - Rizqi, Januar; Fitriawan, Akbar Satria; Widayati, Ririn Wahyu (Jurnal Keperawatan Respati Yogyakarta, 2022)
Wound healing is a complex event involving both cellular and molecular activities. Fibroblasts play an important role and are keys to wound healing through cell proliferation and migration. Honey has anti-microbial, anti-oxidant, anti-inflammatory properties, which are used for various benefits such as wound healing. This study aims to explore the effect of honey on the viability and migration ability of fibroblast cells. The method used is the viability test using the MTT Assay calculated by the formula for the percentage of cell viability. Migration test using In Vitro Wound Scratch Assay. The results of the migration test images were analyzed using ImageJ. Giving honey doses of 0.5% and 0.1% increased cell viability and migration after 24 hours of intervention. Decreased cell viability after 48 hours of treatment, but there was a difference in the meaning of honey 1%, 0.5%, and 0.1% compared to control. Honey doses of 1%, 0.5%, and 0.1% increased fibroblast cell migration compared to control. The lowest honey increases the viability and migration of fibroblasts so that the possibility of wound healing. Keywords: Honey; Fibroblast Migration; Wound Scratch Assay; Wound Healing